Oral Midazolam Premedication for Children Undergoing General Anaesthesia for Dental Care - Saad A. Sheta; Maha AlSarheed (Hindawi Limited, 2009)
Objectives. To assess the efficacy and safety of injectable midazolam administered orally in 3 different doses in children undergoing complete dental rehabilitation under GA. Subjects and Methods. 60 children aged 2-6 years were enrolled in the study. The children were randomly assigned to one of 3 groups and received orally 0.5, 0.75, or 1.0 mg/kg of injectable midazolam mixed with apple juice 30 minutes before separation from parents. The following measurements were assessed: patient's acceptance of the medication, reaction to separation from parents, sedation scores, and recovery conditions. Results. More children were comfortable with parent separation in the group that received the 1.0 mg/kg dose (90%) compared to the group that received the 0.75 mg/kg dose (75%) and the group that received the 0.5 mg/kg dose (55%). The number of children who had desirable sedation was similar in the 0.75 mg/kg and 1.0 mg/kg dose groups. Twenty five percent of the children in the group that received the 0.5 mg/kg dose did not allow venepuncture before induction of GA, and induction of GA was poor for 20% of the children in this group. An increasing number of children scored excellent in terms of ease of venepuncture in 0.75 mg/kg dose group (10%) and in the 1.0 mg/kg dose group (20%) and in terms of induction of GA, 25% and 35%, respectively. Recovery of spontaneous ventilation and extubation was delayed by over 15 minutes in 2 children in the 1.0 mg/kg dose group. Conclusion. The dose of 0.75 mg/kg of injectable midazolam given orally as premedication is acceptable, effective, and safe.